Development aid and international politics: Does membership on the UN Security Council influence World Bank decisions? - Dreher, Axel; Sturm, Jan-Egbert; Vreeland, James Raymond (Journal of development economics, 2009)
We investigate whether elected members of the UN Security Council receive favorable treatment from the World Bank, using panel data for 157 countries over the period 1970-2004. Our results indicate a robust positive relationship between temporary UN Security Council membership and the number of World Bank projects a country receives, even after accounting for economic and political factors, as well as regional, country and year effects. The size of World Bank loans, however, is not affected by UN Security Council membership.
Available online 16 February 2008
Gesehen am 14.05.2019